(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2008)
The antimicrobial activity of methanol extracts of 17 plant species of Bangladesh was evaluated by the agar disc diffusion method. Among those, eight plant extracts exhibited potent antimicrobial activity against a wide variety of Gram positive and Gram negative bacteria and fungi at a concentration of 400 Î¼g /disc. Key words: Antimicrobial activity, Disc diffusion method. DOI = 10.3329/dujps.v7i1.1213 Dhaka Univ. J. Pharm. Sci. 7(1): 23-26, 2008 (June)